Wolbachia promotes successful sex with siblings in the parasitoid Habrobracon hebetor - Bagheri, Zeynab; Talebi, Ali Asghar; Asgari, Sassan; Mehrabadi, Mohammad (Pest management science, 2022)
BACKGROUND Wolbachia are intracellular α‐proteobacteria that have a wide distribution among various arthropods and nematodes. They affect the host reproduction favoring their maternal transmission, which sets up a potential conflict in inbreeding situations when the host avoids sexual reproduction preventing inbreeding depression, while Wolbachia pushes it. We used the wasp Habrobracon hebetor to test the hypothesis that Wolbachia modulates inbreeding avoidance behavior and promotes sib mating. RESULTS Our results showed no obvious pre‐copulatory inbreeding avoidance in this wasp. However, H. hebetor showed a strong post‐copulatory inbreeding avoidance behavior that resulted in a low fertilization rate of uninfected siblings and therefore high rate of production of male progeny was obtained. We observed higher rates of fertilization success in the Wolbachia‐infected lines that resulted in significantly higher female progeny production compared to the uninfected sib mates. Since diploid females are the result of successful fertilization due to haplodiploidy sex determination system in this insect, our results indicate that Wolbachia promoted fertile sib mating in H. hebetor. Interestingly, the rate of adult emergence in the progeny of Wolbachia‐infected sib mates were almost similar to the non‐sib mate crosses and significantly more than those observed in the uninfected sib mate crosses. CONCLUSION Our results support the idea that Wolbachia modulates inbreeding avoidance and promotes sib mating and also mitigates inbreeding depression. By promoting successful sex with siblings and increasing the probability of female progeny, Wolbachia enhances its transmission to the next generation. This is an undescribed effect of Wolbachia on the host reproduction. © 2021 Society of Chemical Industry. Wolbachia subverts inbreeding avoidance. The wasp siblings infected with Wolbachia show higher rates of fertilization success and higher adult emergence rates compared to the uninfected sib mates.